Benzalkonium chloride: A systematic review of its environmental entry through wastewater treatment, potential impact, and mitigation strategies. Issue 15 (3rd August 2022) - Barber, Olivia Williams; Hartmann, Erica M.
Abstract: Benzalkonium chloride is a concern because of its widespread use combined with environmental impacts. It has been found throughout the built and natural environment in wastewater influent, effluent, biosolids, surface water and groundwater. Once benzalkonium chloride enters the environment, it can be lethal to aquatic organisms and invoke antimicrobial resistance. Resistance is a particular concern in the food industry, where benzalkonium chloride is used as a disinfectant. Disinfectants are used liberally against biofilms, which require far higher lethal concentrations than planktonic cells and create resistance reservoirs. While the use of benzalkonium chloride in hospitals is justified with careful use, placing it in consumer products such as hand wash is only increasing the likelihood of environmental release. The widespread use of benzalkonium chloride and how we treat the portion that enters wastewater treatment must be reevaluated to create a safer, healthier environment. Graphical abstract: